The Factors Affecting ATLAS Acceptance By Auditors - Eksa Ridwansyah; Umarudin Kurniawan; Ulin Nuha Alfani; Damayanti Damayanti; Rusmianto Rusmianto (Penerbit Goodwood, 2026)
Purpose: This study examines the factors influencing auditors’ acceptance of the Audit Tool and Linked Archive System (ATLAS) application in Public Accounting Firms (KAPs) in Lampung Province, Indonesia, using the Technology Acceptance Model (TAM) framework.Research Methodology: This study used a quantitative approach with multiple linear regression analyses. The sample consisted of public accountants using the ATLAS application in Lampung Province, Indonesia. Data were collected via online questionnaires, and SPSS was used for analysis to identify the factors affecting ATLAS usage.Results: The results show that Perceived Ease of Use has a positive and significant effect on Actual Use (p < 0.001). Meanwhile, Perceived Usefulness (p = 0.514), Attitude Toward Using (p = 0.119), and Behavioral Intention (p = 0.089) did not significantly affect Actual Use. The regression model explains 55.5% of the variation in ATLAS acceptances.Conclusions: The findings indicate that ease of use is the primary factor influencing auditors’ acceptance of the ATLAS. Although auditors generally perceive ATLAS as useful and have positive intentions toward its use, these factors do not directly determine actual usage behavior in this study’s context.Limitations: This study focuses only on public accountants working at KAPs in Lampung Province, with a limited number of KAPs using ATLAS in their audit processes.Contributions: This study provides valuable insights for PPPK and IAPI to enhance the ATLAS application for more effective use in auditing practices.